Arsenic-rich shallow groundwater in sandy aquifer systems buffered by rising carbonate waters: A geochemical case study from Mannar Island, Sri Lanka - Bandara, Udanekath Chaminda; Diyabalanage, Davindu Saranga; Hanke, Christian; van Geldern, Robert; Chandrajith, Rohana; Barth, Johannes (Science of the Total Environment, 2018)

Assessment of land subsidence mechanisms triggered by dolomitic marble dissolution from hydrogeochemistry and stable isotopes of spring waters - Chandrajith, Rohana; Jayasena, H. A. H.; van Geldern, Robert; Barth, Johannes (Applied Geochemistry, 2015)

Controls of evaporative irrigation return flows in comparison to seawater intrusion in coastal karstic aquifers in northern Sri Lanka: Evidence from solutes and stable isotopes - Chandrajith, Rohana; Diyabalanage, Saranga; Premathilake, K. M.; Hanke, Christian; van Geldern, Robert; Barth, Johannes (Science of the Total Environment, 2016)

Litho-climatic influences on groundwater geochemistry in Sri Lanka - Senarathne, Sachintha Lakshan; Barth, Johannes; van Geldern, Robert; Chandrajith, Rohana (Groundwater for Sustainable Development, 2024)
We present a preliminary investigation of geological, climatic and anthropogenic influences on groundwater geochemistry in Sri Lanka. This spatially confined island of about 65,000 km2 offers excellent boundary conditions for such an overview because it can be separated into two major geological and three climatic domains. Summary parameters, including electrical conductivity (EC) and total hardness (TH), were chosen as best proxies because they belong to the most frequently measured parameters of this data set. Groundwater quality data are presented from a total of 1318 groundwater samples. They were grouped into selected geo-climatic domains. Groundwater in the dry zone showed higher median EC and TH values (740 μS cm−1 and 199 mg L−1) when compared to the intermediate (400 μS cm−1 and 120 mg L−1) and wet zones (146 μScm−1 and 53 mg L−1). The sedimentary terrain of the county could be characterized by the highest median EC and TH values (1006 μS cm−1 and 261 mg L−1). In the metamorphic terrain that covers over 90% of the island, EC and TH values showed the strongest spatial variations that likely depend on climatic conditions. A correlation between EC and TH correlated with an r of +0.70. This trend suggests that EC can also serve as a robust indirect indicator of groundwater TH. Excessive evaporation, seawater intrusion and agricultural return flows affect groundwater quality, mostly in coastal regions, where freshwater demand increases. Sustainable groundwater management demands continuous and comprehensive monitoring of spatial and temporal fluctuations of groundwater. We also propose managed aquifer recharge to protect the long-term sustainability of groundwater in both sedimentary and metamorphic domains. This becomes particularly important under projected climate change scenarios in which drier regions in the country are expected to expand.
CRIS-Team Scopus Importer:2024-05-03
Keywords: Climate change; Electrical conductivity; Geo-climatic regions; Groundwater geochemistry; Total hardness

Unexpected contributions by carbonates and organic matter in a silicate-dominated tropical catchment: An isotope approach - Senarathne, Sachintha Lakshan; van Geldern, Robert; Chandrajith, Rohana; Barth, Johannes (Science of the Total Environment, 2024)
The understanding of global carbon has rarely extended to small-scale tropical river basins. To address these uncertainties, this study aims to investigate the importance of rock weathering and organic matter turnover in the carbon cycle in a terrain dominated by crystalline silicate rocks. The geochemical composition of the dissolved and particulate carbon phases (DIC, DOC and POC) and their stable carbon isotopes were studied in the Deduru Oya River in Sri Lanka. Dissolved inorganic carbon (DIC) was the most dominant carbon phase and its contribution to the total carbon pool varied between 67 and 89 %. Furthermore, the δ13CDIC values in the river varied between −1.1 and −16.5 ‰. The lithological characteristics and molar ratios between Ca2+, Mg2+ and HCO3− indicated rock weathering mainly by CO2 and carbonic acid. The δ13CDIC values for groundwater input were −15.9 ‰, while for carbonate weathering, mainly due to fertiliser input, they reached a value of −12.7 ‰. This input was fed into an isotope mass balance to determine the relative contributions. However, the isotope mass balance was only plausible after correcting for the effects on δ13CDIC caused by degassing and photosynthesis. Our study demonstrated that carbonate weathering and organic matter turnover are essential components of the river carbon cycle even in a silicate dominated catchment. They can represent up to 60 % of the DIC pool. Combined with the higher organic matter turnover and high pCO2 in the river water, it can be suggested that the Deduru Oya River acts as a net source of CO2 in the atmosphere. Our study shows that CO2 degassing and in-stream photosynthesis in tropical river systems need to be considered along with chemical weathering to account for carbon transport and turnover in tropical rivers.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Carbon species; CO; Deduru Oya; Isotope geochemistry; Organic matter; Rock weathering